THE HEART OF NURSING: STORIES FROM THE CLINICAL ODYSSEY - NARRATIVES OF NURSING STUDENTS - Ibrahim, Aisha Mohamed Mahmoud (Research Journal of Health, Medicine and Nursing, 2024)
Effective clinical training is a vital component of nursing education, influencing the quality and competence of future nursing professionals. Nursing students require highquality clinical experiences to bridge the gap between theory and practice. This study aims to investigate the multifaceted nature of nursing students' clinical training experiences. The clinical environment offers a dynamic and challenging context where students not only learn but also engage in hands-on patient care.